Differences in The Actual Level of Defects and The Final Acceptance Protocols of New Flats and Apartments. (2016) - Dubas, Sebastian; Nowotarski, Piotr
Abstract: Every year in Eastern Europe, especially in Poland, thousands of flats and apartments are ready to move-in. Owners of properties are usually obliged by contract to perform a reception of an apartment from the developer. An execution of this acceptance is governed by contractual arrangements between a contractor and a user of the premises, so that the parties know the circumstances under which such a reception should be made. The article presents basic principles in reporting acceptance of flats, basing on existing legislation. Approach shown in the article is presented from a perspective of reception done with participation of external expert – construction professional, usually invited on behalf of the future owner. The authors for the purpose of this article analyzed selected acceptances of flats. An amount of faults reported in protocols of final acceptance and their actual level revealed during reception were taken into the account. Thanks to an access to the records of experts, after comparing protocols and disclosed defects, authors were able to determine that during the execution of acceptance, significantly more defects are detected than finally put into the official protocol. The authors analyzed those defects that most frequently were not entered in the protocols along with a brief summary of possible causes of the prevalence of such situations, using one of the methods of Lean Management connected with root cause analysis - 5 whys.